On the severe convective storm of 29 October 2013 in the Balearic Islands: observational and numerical study. (21st August 2014) - Romero, R.; Ramis, C.; Homar, V.
<x xml:space="preserve">Abstract</x> On 29 October 2013, a severe squall line developed to the west of the Balearic Islands (Spain) ahead of an advancing cold front and then crossed the archipelago. We first provide an observational characterization of the event based on surface reports, remote sensing products, radiosoundings and synoptic information. We also achieve, by means of numerical experiments, new insights into the kinematic and thermodynamic factors that governed the genesis and evolution of the linear convective system. Radar and satellite images confirm the fast movement and linear shape of the system, with an indication of a possible transition into a bow‐echo structure during its later stages. The synoptic setting at mid‐upper tropospheric levels was dominated by a cold trough extended over western Europe, associated with a jet stream located downstream. Convection evolved under the right entrance region of the jet and initiated under the crucial influence of a surface low that developed over the Mediterranean Sea ahead of the cold front. The low not only cooperated with the upper‐level dynamical forcing to erode a capping inversion initially present over the Balearics and moisten the atmospheric column above, but also shaped and enhanced a convergence line along which the first convective cells grew and self‐aggregated. This scenario is confirmed by numerical simulations of the case, which also emphasize the important role of regional topography in the production of the aforementioned maritime convergence through the mesoscale modulation of the low‐level flow. Additional simulations show that (i) the destabilization of the low‐level air mass necessary for triggering and feeding an organized convective system on 29 October 2013 was attributable to prior evaporation from the Mediterranean and (ii) sea‐surface temperatures appear to be critical for a successful fine‐grid numerical forecast of the mode, degree of severity, timing and track of the convective precipitation system.